In Situ Surface‐Directed Assembly of 2D Metal Nanoplatelets for Drug‐Free Treatment of Antibiotic‐Resistant Bacteria (Adv. Healthcare Mater. 19/2022). Issue 19 (5th October 2022) - Fathi, Parinaz; Roslend, Ayman; Alafeef, Maha; Moitra, Parikshit; Dighe, Ketan; Esch, Mandy B.; Pan, Dipanjan
Abstract : Antibacterials In article 2102567 by Dipanjan Pan and co‐workers, a surface modification technique is used for the direct self‐assembly of 2D copper nanoplatelets onto copper surfaces. These nanoplatelets exhibit antibacterial properties against multi‐drug‐resistant bacteria.